Community structure of benthic molluscs shaped by environmental and ecological variables in the coastal waters of Changle, Fujian Province, China - Liu, Cai-lian; Xu, Qing; Wang, Zhi; Jiang, Xiao-bin; Ding, Guang-mao; Ren, Qing-qiang; Song, Jia-hao; Liu, Min (Frontiers in Marine Science, 2023)
To understand the community structure of benthic molluscs and their relationship under varying environmental and ecological conditions, monthly samplings in AprilSeptember 2019 were conducted at 27 stations in an approximate sea area of 20,600 ha (Changle District, Fujian Province, China). Forty-five species were identified, most as food; six dominant species, all bivalves and commercially important, were determined by the index of relative importance > 500. The average abundance and biomass were 308.32  103 ± 1,156.24  103 ind./km2 and 1,423.71 ± 2,272.37 kg/km2, respectively. Three spatial community groups were identified, named Min River Estuary, Nearshore, and Offshore, with significant differences in species composition and abundance (ANOSIM, p < 0.01). Results of the canonical correlation analysis indicated that the community structure of benthic molluscs was significantly related to water depth, pH, salinity, temperature, phytoplankton abundance and zooplankton abundance (p < 0.1). As the important habitat for benthic molluscs, long-term monitoring in the coastal waters of Changle is needed for sustainable harvest.